The Influence of Pancasila and Citizenship Education on Student Participation in Community Social Activities - Lutfia Nadiroha Harahap (International Journal of Students Education, 2024)
This study aim to explore the influence of Pancasila and citizenship education on student participation in community activities. Research methods used is method literature review. The research sample consisted of from student from various study programs in several college tall. The research results show that Pancasila and citizenship education have a significant positive influence on student participation in community activities. The implication of these findings is the importance of integrating Pancasila values and learning citizenship in curriculum education tall for increase environment students in development public. Advice about influence Pancasila and civic education to participation student in activity society for students at college tall or environment campus can increase. Student will more own more understanding deep about citizenship and developing necessary skills for participation in a way active in activity public.